Impact of Minimum Wage, Inflation, and Economic Growth on Poverty in Yogyakarta Province - Sekarwati, Dias; Priana, Wiwin; Wardaya, Wirya (Journal of Business Management and Economic Development, 2024)
Poverty is a very complex problem caused by many factors. Poverty itself means that individuals lack the ability to fulfill the basic needs of life. Regional autonomy established by Indonesia requires regional governments to manage their respective territories. Yogyakarta Province has the highest poverty rate on the island of Java. Poverty occurs due to microeconomic factors. Minimum wages, inflation rates, and economic growth are among the macroeconomic factors that cause poverty. The aim of this research is to find out how Yogyakarta Province's minimum wage, inflation rate, and economic growth affect the province's poverty level. Panel data regression models are used in this type of quantitative research. Cross-sectional data from districts and cities in Yogyakarta Province for 2009–2023 were used in this study. Based on research findings, the poverty level of DI Yogyakarta Province is largely determined by the minimum wage and economic growth variables, while it is not influenced by the inflation variable.